The Wiley Blackwell Handbook of the Psychology of Training, Development, and Performance Improvement - Kraiger, Kurt, 1957-, editor 207373; Passmore, Jonathan, editor 579084; Malvezzi, Sigmar, editor 636020; Santos, Nuno Rebelo dos, editor 636021 (Chichester, West Sussex : Wiley Blackwell, 2015)
"The Wiley Blackwell Handbook of the Psychology of Training, Development, and Performance Improvement provides up-to-date, contemporary information for researchers and professionals by reviewing the latest literature and research in the interconnected fields of training, development, and performance appraisal. It brings a psychological perspective to bear on a multidisciplinary field that links to management, human resources, and education. Unique to reference works in this area, it maintains a truly global focus on the field with top international contributors looking at research and practice from around the world, including South America, Europe, Canada, and Australia, as well as the United States and the United Kingdom. The chapters cover a diverse range of important contemporary topics, such as needs analysis, job design, active learning, self-regulation, simulation approaches, 360-degree feedback, and virtual learning environments. Together, they offer researchers and professionals essential information for building a talented organization, a critical and challenging task for organizational success in the twenty-first century."--